2013
DOI: 10.4236/jmmce.2013.11002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation & Characterization of Al-5083 Alloy Composites

Abstract: This paper reports the dry sliding wear behavior & Brinell hardness test of AA 5083 aluminium reinforced with SiC particles fabricated by stir casting technique. Different volume fraction of SiC particles (3, 5 and 7 wt%) were used for synthesis. The wear test has been conducted on pin-on-disc testing machine to examine the wear behaviour of the aluminium alloy and its composites. An attempt has been made to study the influence of wear parameters like applied load, sliding speed, sliding distance and percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, as the tool rotated faster at much higher speeds, there was an increase in heat input that helped the composite's flow characteristics improve and reduced tool wear. In a different investigation for dry sliding wear of AA5083 alloy [134], the material loss rate was higher at low speeds. Also, it was noted that the material loss rate decreased when running velocity raised.…”
Section: Influence Of Sliding Speedmentioning
confidence: 92%
“…However, as the tool rotated faster at much higher speeds, there was an increase in heat input that helped the composite's flow characteristics improve and reduced tool wear. In a different investigation for dry sliding wear of AA5083 alloy [134], the material loss rate was higher at low speeds. Also, it was noted that the material loss rate decreased when running velocity raised.…”
Section: Influence Of Sliding Speedmentioning
confidence: 92%
“…Factors such as applied load and relative slip were less influential. The addition of reinforcements to MMCs can limit the flow of plastic deformation [85,86].…”
Section: Fretting Wearmentioning
confidence: 99%
“…However, most studies have concentrated on the tribological properties rather than pure mechanical response. GARGATTE et al [6] used liquid stir casting method to add SiC particles to Al-5083 and showed that the reinforcements reduce the wear rate when compared to pure alloy. The same has been corroborated by SOLEYMANI et al [7] not just with SiC, but also with MoS 2 reinforcements.…”
Section: Introductionmentioning
confidence: 99%